Cattech: warm cat shelter / Muhammad Firdaus Ismail … [et al.] - Ismail, Muhammad Firdaus; Mustafa Bakri, Muhammad Syahriezlan; Erwan Erizull, Muhammad Iqmal Hakimi; Abdul Karim, Nurull Tasnim; Tukimin, Nur Insyirah; Rosli, Nurul Hazieqa (2023)
The New Product Development Report for the Warm Cat Shelter outlines the comprehensive process of developing a shelter designed to provide a comfortable and warm environment for outdoor and stray cats during cold or rainy weather. It includes an executive summary, introduction, problem statement, methodology, new product development details, and a conclusion. The development process involved thorough research, concept testing, prototype development, and test marketing. Surveys and questionnaires were utilized to gather feedback from potential consumers, with a focus on understanding market trends, customer needs, and competition. This report emphasizes the importance of considering the well-being, comfort, and safety of cats in the development of the product. The Warm Cat Shelter aims to address the need for a safe and warm environment for cats, providing comfort and safety for both outdoor and home cats. There is also highlights the positive reception of the Warm Cat Shelter concept and the potential for its success in the market. Additionally, it emphasizes the importance of understanding market trends, customer needs, and competition in the development of new products. The document provides a detailed and insightful overview of the development process for the Warm Cat Shelter, including its purpose, benefits, limitations, and the thorough research and testing conducted to assess its market potential.